An empirical method for rapidly estimating the loading distributions on swept back wings - Stanton Jones, R. (Cranfield College of Aeronautics, 1950)
This paper describes the derivation of empirical formulae for the loading distribution on straight tapered swept back wings, in terms of the parameters governing the geometric wing plan form. The derivation is based mainly on the results of the Weissinger method but corrections to give better agreement with experimental results have been introduced.